The Efficacy of Thrombolytic Therapy in Inferior Myocardial Infarction with Damage to the Right Ventricular - E. S. Mazur; V. V. Mazur; N. S. Kuznetsova; R. M. Rabinovich; K. S. Myasnikov (Рациональная фармакотерапия в кардиологии)
Aim. To study the results of thrombolytic therapy and accuracy of electrocardiographic assessment of thrombolysis efficiency in inferior myocardial infarction with and without right ventricular lesion.Material and methods. The118 patients with inferior myocardial infarction were included in this study. They received TLT in the first 12 hours of the disease. The dynamics of ST-segment in 90 minutes from the TLT start and coronary angiography data were analyzed.Results. Right ventricular myocardial infarction (RVMI) was diagnosed in 49 (41.5%) of 118 patients by echocardiography. Patients with and without RVMI did not differ in age, gender and comorbidities, but patients with RVMI were more likely to have arterial hypotension, atrioventricular block, and atrial fibrillation. All patients with RVMI had occlusion of the right coronary artery (RCA) in the proximal (34.7%) or medial segment (65.3%). Occlusion of the circumflex coronary artery was found in 20 (29.0%) patients without RVMI, and RCA occlusion - in other patients. The infarction-associated artery blood flow equal TIMI 2-3 was found in 17 (34.7%) patients with RVMI and in 46 (66.7%) patients without RVMI (p<0.005). ST-segment decrease by 50% or more in 90 minutes from the TLT was found in 35 (71.4%) patients with RVMI and in 49 (71.0%) patients without RVMI (p>0.05). The false-positive assessment of thrombolysis efficiency was noted in patients with and without RVMI in 21 (42.9%) and 11 (15.9%) cases (p <0.005), respectively. There were no false-positive assessments in patients with RVMI when using ST-segment decrease to the isoline.Conclusion. TLT should be considered effective in patients with inferior myocardial infarction with the right ventricle lesion, if ST-segment decreases to isoline in 90 minutes from the TLT start.